Enteroparasites in Children With Moderate Malnutrition Treated in Two Hospitals in the City of Maracaibo - Ellen Acurero Yamarte; Marinella Calchi La Corte; Zulbey Rivero Rodríguez; Angela Bracho Mora; Adriana Maldonado Ibañez; Miguel Reyes; Belisa Vergara; Ana Velazco (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
Objective: To determine the prevalence of intestinal parasites in moderately malnourished children treated at two hospitals in the city of Maracaibo, State of Zulia. Materials and Methods: Eighty-four fecal samples from moderately malnourished children of both sexes between 8 months and 12 years of age, hospitalized in the Nutrition Rehabilitation Unit of the Chiquinquirá Hospital and South General Hospital, Dr. Pedro Iturbe, were analyzed. Each fecal specimen underwent a fresh test with saline solution 0.85%, Lugol staining and Ritchie concentrate. Results: An overall prevalence of parasitized children (58%) was observed; 34.52% were female, 23.81% were male. There was a predominance of monoparasitism 57.14%. Regarding the age group, the 3 to 6 stratum was most heavily parasitized (30. 95%). The X2 revealed a significant relationship between parasitism and age. Species found in the group under study were: Blastocystis spp. (49. 39%), Giardia intestinalis (21.52%), Entamoeba histolytica/dispar/moshkovskii (11.39%), Entamoeba coli (6.33%) and Trichuris trichiura (6.33%). Conclusions: The results are similar to those obtained in previous research. The high prevalence of protozoa suggests a pattern of direct transmission among the studied population or through consumption of water and/or food. The need to evaluate behaviour related to food hygiene and water supply forth estudied population is proposed.